Analisis Indeks Harga Konsumen (IHK) Menurut Kelompok Pengeluaran Nasional Tahun 2018 - Halida Sofiah Noor; Cucu Komala (Jurnal Perspektif, 2019)
The Consumer Price Index is an important indicator of the financial market. The Consumer Price Index (CPI) is an index number that describes changes in prices of goods and services consumed by the public in general for a certain period with a predetermined time period. National expenditure according to CPI is divided into four sub-groups, namely the first general sub-group, the second sub-group of foodstuffs the third sub-group of processed foods, beverages, cigarettes and tobacco and fourth sub-group housing, water, electricity, gas and fuel development CPI 2018, every month from January to December tends to increase. Changes in CPI can describe the rate of increase (inflation) or the rate of decline (deflation) of goods or services. CPI can be regarded as a very important economic indicator and is used to represent changes in the average retail price level at the consumer level for a number of certain types of goods and services. The rise in the CPI can lead to an increase in interest rates, increase in money supply growth, increase the attractiveness of currencies, and increase inflation.